Study on display sequences in Cotton Pygmy-Goose Nettapus Coromandelianus Coromandelianus Gmelin - Sanjib Upadhyaya; PK, Saikia (Journal of Research in Biology, 2011)
The pairing and display sequence of Cotton Pygmy-goose (Nettapus coromandelianus coromandelianus Gmelin) in Eastern Assam was observed from April 2007 to July 2008. The frequency of head movement (up-down and left-right) are found to be 0.288 and 0.28 per second. Courtship bouts occurred in groups averaging 5.7 birds, with a male: female ratio of 1.1:1. Several new displays and vocalizations are described. Early pair bonds appeared tenuous and were continually tested until nest-searching activities began in May. Birds in groups displayed and vocalized more than paired birds, and birds displayed and vocalized more or less equally throughout the period with mild rainy climate. Early pairing may be related to a bird’s condition, climatic condition, success in obtaining a nesting site, and increased productivity